γ-Aminobutyric Acid and Zeolite as Natural Treatments to Maintain the Fruit Quality, Storability, and Shelf Life in Apricot - Abdullah Alebidi; Hayam M. Elmenofy; Mahmoud Abdel-Sattar; Mahmoud G. Abd El-Gawad; Hatem R. M. Kotb; Hail Z. Rihan; Hoda Galal; Abdel-Moety Salama (BioResources, 2025)
The global trend promotes using natural and eco-friendly materials to improve fruit quality and storability. This study was carried out to examine the impact of pre-harvest spraying of γ-aminobutyric acid (GABA) at 1.0 and 2.0 mmol/L, and post-harvest zeolite dipping (3% and 6% levels), on the quality of apricot fruits stored at 0±1 °C and 90-95% relative humidity. The results indicated that different levels of GABA and zeolite treatments significantly reduced the respiration rate, decay percentage, and fruit weight loss of stored apricots. Moreover, all experimental treatments notably slowed down the changes in fruit firmness, total soluble solid content, total sugars, total acidity, total phenols, and ascorbic acid, compared to the control. Applying GABA and zeolite evidently decreased the activities of pectin methylesterase and polyphenol oxidase enzymes. On the other hand, they increased the peroxidase activity compared to the control treatment for both seasons. Moreover, the application of zeolite and GABA at a concentration of 6% and 2 mmol/L, respectively, are recommended to enhance the storability and extend the shelf life of ‘Canino’ apricot fruits and preserve their quality. This study contributes to the Sustainable Development aims by reducing postharvest losses, food waste, and increasing marketability, as well as supporting food security by conserving resources and increasing marketing income.